Dental fear: a narrative review - Nishi, Nowrin J.; Pervin, Shahana; Shaude, Syed (International Journal of Research in Medical Sciences, 2022)
The dental fear and anxiety (DFA) is a common phenomenon around the world. From children to the adults, most of the people become frightened when they face any dental discomfort and they need to visit a dentist and go through a treatment procedure in a dental set up. This narrative review tends to identify the causes behind DFA, its consequences and management of DFA from different studies which were conducted previously. This study is a narrative review of DFA. This study is mainly based on the secondary data from different articles and journals which were available online. After the proper screening from 154 titles, the final review included 68 articles. Based on different studies, it is found that DFA in quiet common in the people of all ages. The studies had found that dental fear and anxiety most often results from a traumatic past dental experience. Friendly dental office environment is an effective way in reducing dental fear and anxiety. Psychotherapeutic management is also important is managing DFA like behavior-management techniques, relaxation techniques, distraction, guided imagery, hypnotherapy, acupuncture, systematic desensitization or exposure therapy, positive reinforcement, cognitive restructuring and pharmacological management. The techniques for managing DFA can be the effective solution for reducing stress and make the treatment process more comfortable.